E-Government and websites : a public solutions handbook - Manoharan, Aroon (ed.) (New York Rouledge, 2015)
This book presents a citizen-centric perspective of the dual components of e-government and e-governance. E-government refers to the practice of online public reporting by government to citizens, and to service delivery via the Internet. E-governance represents the initiatives for citizens to participate and provide their opinion on government websites. This volume in the Public Solutions Handbook Series focuses on various e-government initiatives from the United States and abroad, and will help guide public service practitioners in their transformation to e-government. The book provides important recommendations and suggestions oriented towards practitioners, and makes a significant contribution to e-government by showcasing successful models and highlighting the lessons learned in the implementation processes. Chapter coverage includes: * Online fiscal transparency * Performance reporting * Improving citizen participation * Privacy issues in e-governance * Internet voting * E-government at the local level
Keywords: Public administration-Technological innovations; Electronic government information